Avaliação dos efeitos do 2-nitrato-1,3- dibutoxipropano (NDBP) sobre o sistema cardiovascular - Silva, Maria do Socorro de França (2012)
Previous studies have shown that the 2-nitrate-1,3-dibuthoxypropan (NDBP), an organic nitrate synthesized from glycerin, induced vasorelaxation in mesenteric artery of rats through activation of the NO-cGMP-PKG pathway and K+ channels, in addition, caused hypotension and bradycardia in normotensive conscious rats. The current research aimed to investigate the effects of the NDBP on cardiovascular system in rats, evaluating the NO release in rat smooth muscle cell culture, the ability of NDBP to induce tolerance to vasodilatation and the effect of the acute administration of the compound on autonomic control of blood pressure and heart rate of normotensive and hypertensive rats, using in vitro and in vivo approaches. For biochemical determination aortic rat smooth muscle cell culture (ARSMC) was used and the pharmacological experiments were developed using Wistar rats or spontaneously hypertensive (SHR) and normotensive Wistar Kyoto (WKY) rats. The NDBP caused concentration-dependent increases in NO levels in ARSMC. In addition, NDBP produced no change in the vasorelaxation induced by the NDBP when the rings were pre-incubated with the NDBP (10 μM or 100 μM), suggesting that the NDBP did not induce tolerance. In vivo experiments, SHR rats were significantly hypertensive compared with WKY rats. The acute administration of the NDBP (1, 5, 10, 15 and 20 mg/kg, i.v.) caused a biphasic response: hypotension and bradycardia followed by hypertension and tachycardia in WKY and SHR rats. The blockade of muscarinic receptors with atropine (2 mg/kg) blunted the bradycardia induced by NDBP (15 mg/kg) and reduced the hypotension in WKY and SHR. However, the pressor response to the compound was potentiated. Furthermore, vagotomy almost abolished the bradycardia in WKY and SHR. Moreover, hexamethonium (30 mg/kg), a nicotinic ganglionic blocker, reduced both bradycardia and pressor response in WKY and SHR. The administration of methylene blue (4 mg/kg), a soluble guanylyl cyclase (sGC) blocker, attenuated the hypotension and bradycardia induced by the NDBP (15 mg/kg) in WKY. Similar event occurred in SHR animals. In conclusion, the NDBP releases NO in ARSMC, and was unable to induce tolerance to its vasorelaxant effect, however, the cardiovascular effects of NDBP are mainly mediated by the central action of the compound, resulting in changes on autonomic function of spontaneously hypertensive and normotensive rats.